2023
DOI: 10.3389/fcvm.2023.1116861
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between nonalcoholic fatty liver disease and atherosclerotic cardiovascular disease

Abstract: Therapeutic approaches that lower circulating low-density lipoprotein (LDL)-cholesterol significantly reduced the burden of cardiovascular disease over the last decades. However, the persistent rise in the obesity epidemic is beginning to reverse this decline. Alongside obesity, the incidence of nonalcoholic fatty liver disease (NAFLD) has substantially increased in the last three decades. Currently, approximately one third of world population is affected by NAFLD. Notably, the presence of NAFLD and particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 448 publications
(564 reference statements)
0
7
0
1
Order By: Relevance
“…It will also be important to determine the particular mechanisms involved. A key initial focus should be to understand if the higher serum and liver triglyceride levels are related and the direction of this relationship, especially given that there seems to be an existing relationship between liver and serum triglyceride levels as shown in other studies (Finney et al, 2023). Of note, there was not an effect of early life macronutrient levels on serum and liver cholesterol levels.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It will also be important to determine the particular mechanisms involved. A key initial focus should be to understand if the higher serum and liver triglyceride levels are related and the direction of this relationship, especially given that there seems to be an existing relationship between liver and serum triglyceride levels as shown in other studies (Finney et al, 2023). Of note, there was not an effect of early life macronutrient levels on serum and liver cholesterol levels.…”
Section: Discussionmentioning
confidence: 97%
“…This is consistent with previous studies showing that the gestational and nursing nutritional periods can affect lipid homeostasis in adults (Alfaradhi et al, 2014) and here we show that this is also true for the post-nursing early childhood-adulthood period. This is important as dyslipidaemia is a risk factor for prominent age-related diseases, particularly atherosclerotic cardiovascular disease and non-alcoholic fatty liver disease (Finney et al, 2023). Again, it will be important to determine whether high-fat feeding in this particular early life period stably affects dyslipidaemia-related disease risk in later life using appropriate animal models.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting results related to the role of SIRT4 in the development of atherosclerosis, which is strongly associated with NAFLD [ 144 ] and heavy alcohol consumption [ 145 ]. SIRT4 overexpression suppressed the PI3K/Akt/NF‑κB pathway by inhibiting PI3K phosphorylation and phosphorylated (p)‑Akt and inhibiting the expression of inflammatory cytokines in oxidized low-density lipoprotein‑induced human umbilical vein endothelial cells [ 146 ].…”
Section: Sirtuins: As Therapeutic Targetsmentioning
confidence: 99%
“…CVD risk increases with the presence of hepatic steatosis and stage of fatty liver disease[ 49 , 50 ]. A meta-analysis of observational studies including 34043 participants with diagnosis of MASLD confirmed an associated higher risk of cardiometabolic complications.…”
Section: Introductionmentioning
confidence: 99%
“…TM6SF2 rs58542926 T-allele–mediated hepatic retention of TGs and cholesterol predispose patients to MASLD-related fibrosis, whereas C-allele carriage promotes VLDL excretion, thus increasing the risk of CVD or atherosclerosis while protecting the liver[ 43 , 58 ]. Also, similar to TM6SF2 mutation, PNPLA3 rs738409 G allele is associated with a low risk of cardiovascular events, owing to the tight association with lower serum LDL level, as low LDL-C and high HDL-C are cardioprotective[ 50 , 59 ].…”
Section: Introductionmentioning
confidence: 99%